Ξ hypernuclear states predicted by next-to-leading-order chiral baryon–baryon interactions. (4th September 2021) - Kohno, M; Miyagawa, K
Abstract: The $Ξ$ single-particle potential obtained in nuclear matter with next-to-leading-order baryon–baryon interactions in chiral effective field theory is applied to finite nuclei by an improved local-density approximation method. As a premise, phase shifts of $Ξ N$ elastic scattering and the results of Faddeev calculations for the $Ξ NN$ bound state problem are presented to show the properties of the $Ξ N$ interactions in the present parametrization. First, the $Ξ$ states in $^{14}$ N are revisited because of recent experimental progress, including discussion on the $Ξ N$ spin–orbit interaction that is relevant to the location of the $p$ -state. Then the $Ξ$ levels in $^{56}$ Fe are calculated. In particular, the level shift which is expected to be measured experimentally in the near future is predicted. The smallness of the imaginary part of the $Ξ$ single-particle potential is explicitly demonstrated.